MIS Management Information Systems - Bidgoli, Hossein (Cengage, 2024)
With its practically focused approach, Bidgoli's MIS 11 helps you explore MIS concepts and advancements that will enhance your personal and professional success. Over 130 real-life information boxes and cases illustrate how the materials covered in the text positively impact your everyday life as well as future career. With this edition's MindTap digital experience, you can strengthen your decision-making skills with "You Make the Decision" interactive case studies that bridge technology and business strategy -- with you as the decision-maker. New concept videos and foundational case studies help you delve deeper into key course concepts, while the micro-course on SQL fundamentals gives you hands-on coding experience. In addition, MindTap's MIS for Life spotlights the latest developments and trends in today's dynamic business world.